The survival outcomes of neoadjuvant sintilimab combined with chemotherapy in patients with locally advanced esophageal squamous cell carcinoma - Lv, Huilai; Huang, Chao; Li, Jiachen; Zhang, Fan; Gai, Chunyue; Liu, Zhao; Xu, Shi; Wang, Mingbo; Li, Zhenhua; Tian, Ziqiang (Frontiers in Immunology, 2023)
Background Neoadjuvant programmed death receptor-1 (PD-1) inhibitor combined with chemotherapy has been reported to improve the pathological response of locally advanced esophageal squamous cell carcinoma (ESCC), but the systematic report on survival follow-up is quite few. This study we will report the survival follow-up outcomes after a median follow-up of 21.1 months. Methods This was a real-world retrospective study. Locally advanced ESCC patients treated with neoadjuvant sintilimab combined with albumin-bound paclitaxel and nedaplatin followed by surgery and completed at least 1-year follow-up were reviewed. The primary outcome was disease-free survival (DFS) at 24 months. The secondary outcome was overall survival (OS) at 24 months. Results Ninety eligible patients were included in the analysis between July 2019 and October 2021. The median number of neoadjuvant cycles was 3 (range 2-4). All patients achieved R0 resection. With a median follow-up of 21.1 months (range 14.0-39.0), the median DFS and median OS had not reached, 2-year DFS rate was 78.3% (95%CI 68.8%-89.1%) and 2-years OS rate was 88.0% (95%CI 80.6%-96.0%). Postoperative pathological stage, pCR, MPR, tumor down-staging were significantly correlated with favorable survival outcome. Univariable and multivariable Cox regression analysis identified cycle number of neoadjuvant treatment as independent predictor of DFS. Conclusion Our results preliminarily show a survival benefit of neoadjuvant sintilimab combined with chemotherapy in locally advanced ESCC.